2015
DOI: 10.1108/bfj-11-2013-0321
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for organic and fairtrade certified yellow chili peppers

Abstract: Purpose -The purpose of this paper is to evaluate the consumers' preferences in middle-and highincome districts in Lima for three organic and Fairtrade certification attributes: environmental protection, production without pesticides, and improvement in the quality of life of farmers. Yellow chili pepper was used as case study. Design/methodology/approach -A survey of 183 households was conducted among the population located in middle and high income districts in Lima, because of their higher ability to pay. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
2
16
1
2
Order By: Relevance
“…Mean and median WTP from both stated and realized preference methods were positive, indicating respondents’ demand for the environmental attribute of shade‐grown coffee. Our results are consistent with other studies indicating a high stated WTP for social and environmental attributes (Bearse, ; D'Souza, Taghian, & Lamb, ; Didier & Lucie, ; Garcia‐Yi, ; Rousseau, ). Approximately a fifth of the mean WTP for natural, regionally produced beef was explained by concern for supporting local agriculture and environmental benefits (Umberger, McFadden, & Smith, ).…”
Section: Discussionsupporting
confidence: 92%
“…Mean and median WTP from both stated and realized preference methods were positive, indicating respondents’ demand for the environmental attribute of shade‐grown coffee. Our results are consistent with other studies indicating a high stated WTP for social and environmental attributes (Bearse, ; D'Souza, Taghian, & Lamb, ; Didier & Lucie, ; Garcia‐Yi, ; Rousseau, ). Approximately a fifth of the mean WTP for natural, regionally produced beef was explained by concern for supporting local agriculture and environmental benefits (Umberger, McFadden, & Smith, ).…”
Section: Discussionsupporting
confidence: 92%
“…In general, the high consumer acceptance of organic labels which can be observed for the food market in Germany [7,69] does not seem to correspond with analogous consumers' preferences for non-edible organic products. As some studies related to the food sector showed that consumers' preference for an organic label mainly depend on their perceived positive health aspects [24,25,70], it can be assumed that health aspects are being less important related to non-edible products like cut roses thus leading to lower preferences of the Bioland labelled roses. Additionally, Loureiro and Lotade [71] argued that consumers were not quite aware or could barely imagine the environmental impact of coffee cultivations in distant regions, what might be also transferable to the analyzed cut roses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is no conclusion on whether WTP for fair trade is lower (or higher) than that of organic label. More specifically, while both Rousseau [33] and Loureiro et al [35] reported higher premiums for the fair trade label in the Belgian chocolate and the American coffee consumers respectively, organic label was reported to have higher premiums by both Van Loo et al [36] (US coffee consumers) and Garcia-Yi [48] (Peruvian yellow chili peppers consumers). Yet still, Didier et al [40] obtained similar premiums for the two labels in the French chocolate consumers.…”
Section: Willingness To Pay For Fair Trade and Organic Labelsmentioning
confidence: 94%
“…Some other studies have studied fair trade and organic labels simultaneously [33][34][35][36]40,42,[47][48][49]. These studies have been motivated by several factors.…”
Section: Willingness To Pay For Fair Trade and Organic Labelsmentioning
confidence: 99%